From High School Curriculum to Literacy Network: Transforming High School English Teaching in California. Issue 6 (24th April 2019) - Brynelson, Nancy; Fletcher, Jennifer; Graff, Nelson
Abstract : This department focuses on literacy leaders, including school and instructional leaders, teachers, and external partners, who are working to improve outcomes for adolescent and adult learners in a wide range of education settings. Columns investigate the challenges and complexities inherent in such work and share lessons learned, impactful strategies and approaches, and promising pathways forward.